2022
DOI: 10.1002/ep.13864
|View full text |Cite
|
Sign up to set email alerts
|

Efficient performance of copper oxide nanoparticles synthesized with pomegranate leaf extract for neutral red dye adsorption

Abstract: The adsorption of dyes in water and wastewater using metallic nanoparticles stands out due to its high removal capacity and low environmental impact. The present study proposed the use of copper oxide nanoparticles (CuO_NP), synthesized with pomegranate leaves extract (Punica granatum) to remove the neutral red (NR) dye from the aqueous medium. The characterization confirmed the efficiency of the redox process and the formation of nanoparticles. The adsorption results were promising, wherein the maximum adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 81 publications
4
6
0
Order By: Relevance
“…The result indicated that the biosynthesized CuONPs were effectively regenerated and reused for the uptake of both pollutants from solution. This finding is consistent with the reports on the successful reuse of CuONPs for the adsorption of other pollutants from solution 48 , 49 , 54 , 55 .
Figure 11 The regeneration and reuse of the biosynthesized copper oxide nanoparticles for the uptake of thiazolyl blue and paracetamol (pH 8.0 for thiazolyl blue and pH 7.0 for paracetamol; concentration 100 mg/L; temperature 300 K, sonication time 120 min).
…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The result indicated that the biosynthesized CuONPs were effectively regenerated and reused for the uptake of both pollutants from solution. This finding is consistent with the reports on the successful reuse of CuONPs for the adsorption of other pollutants from solution 48 , 49 , 54 , 55 .
Figure 11 The regeneration and reuse of the biosynthesized copper oxide nanoparticles for the uptake of thiazolyl blue and paracetamol (pH 8.0 for thiazolyl blue and pH 7.0 for paracetamol; concentration 100 mg/L; temperature 300 K, sonication time 120 min).
…”
Section: Resultssupporting
confidence: 93%
“…Although the model qe value of the PFO model was closer the experimental value, the higher R 2 and lower SSE of the PSO model indicated a greater conformity of the adsorption to the PSO model. The best fit of the PSO model to the process corroborates the findings of most researchers on the uptake of various pollutants on CuONPs 27 , 29 , 32 , 54 , 55 , 58 , 65 – 67 . Therefore, based on its premise, the number of active sites occupied in the adsorbent is proportional how much adsorbate would be absorbed 54 , 55 , 68 .…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations